Предмет: Математика, автор: Lemok

Спростіть вираз-2(2,7x-1)-(6-3,4x)-8(0,4-2)
Якщо х=-5/6

Ответы

Автор ответа: Аноним
3

-2(2,7x-1)-(6-3,4x)-8(0,4-2)=-5.4х+2-6+3.4х-3.2+16=

=-2х+16-4-3.2=-2х+8.8

Якщо х=-5/6, -2х+8.8=2*5/6+44/5=5/3+44/5=(25+132)/15=157/15=10 7/15

Автор ответа: cooolery
1

Ответ:

-9 7/15

Пошаговое объяснение:

-2(2,7×(-5/6)-1)-(6-3,4×(-5/6))-8(0,4-2)= -2(27/10×(-5/6)-1)-(6-34/10×(-5/6))-8×(-1,6)= -2(-27/12-1)-(6-17/6)-12,8= -2(-27/12-12/12)-(36/6-17/6)-12,8= -2×(-39/12)-19/6-128/10=39/6-19/6-128/10=20/6-128/10=100/30-384/30= -284/30= -142/15= -9 7/15

Похожие вопросы
Предмет: Математика, автор: качльки